ʺRole of information technologies in the process of professional preparation of studentslawyers of military-legal facultiesʺ. - Budanov, O. (Problems of Engineer-Pedagogical Education, 2024)
It has been shown that the stagnation of information technologies in all spheres of corporate activity requires radical approaches to change the place and organization of professional education, including military legal education of law cadets at military law faculties lays the foundation for the greatest education in Ukraine. The problems of informatization of the Ukrainian military law school have been identified, in particular: the existence of a unified methodology for the introduction of new information technologies in the initial process of military legal faculties; low level of cooperation and coordination of the activities of military and law faculties of the major educational institutions of Ukraine with the creation of a unified legal and legal framework for software support; insufficient preparation of professorial and educational skills in special departments of military and law faculties, etc. The process of informatization of professional training of legal cadets for future military-legal activities, which is related to us in advance of ensuring the necessary level of technical equipment for the initial process, is examined. with a clear focus on professional legal and legal tasks in the minds of an operational situation, and especially in the extreme minds of a wartime situation. Current realities dictate the need to search for nobles and ways to improve the information literacy of law cadets of military law faculties of the Western Military District of Ukraine. The main directions of intensive informatization of legal information to improve the level of professional training of future military lawyers have been established and named. The systemic development of a complex of information technologies of general and special significance in the initial process of military and law faculties as the foundation of the greater education of Ukraine is described. Options for the integration of information technologies have been proposed in the departments of professional training of law students in the military forces. Particular respect is given to the possibilities of remote training of law cadets during military training in the minds of military personnel. The practical significance of the development of information technologies on the basis of highly automated technologies has been emphasized, which allows optimizing the initial process at the military and law faculties of Ukraine's advanced knowledge for the profession. current training of legal cadets at the highest level of legal tasks in extreme minds of military legal activity for the military regime.